2009
DOI: 10.4049/jimmunol.0900153
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory FcγIIb Receptor Dampens TLR4-Mediated Immune Responses and Is Selectively Up-regulated on Dendritic Cells from Rheumatoid Arthritis Patients with Quiescent Disease

Abstract: Rheumatoid arthritis (RA) is a common autoimmune disease leading to profound disability and premature death. Although a role for FcgammaRs and TLRs is accepted, their precise involvement remains to be elucidated. FcgammaRIIb is an inhibitory FcR important in the maintenance of tolerance. We hypothesized that the inhibitory FcgammaRIIb inhibits TLR responses on monocyte-derived dendritic cells (DC) and serves as a counterregulatory mechanism to dampen inflammation, and we surmised that this mechanism might be d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 62 publications
5
56
1
1
Order By: Relevance
“…Consistently, an FcγRIIB defi ciency can lead to overwhelming infl ammation as evidenced by the increased susceptibility to EAE shown by FcγRIIB knockout mice (Kalergis and Ravetch 2002;Iruretagoyena, Riedel et al 2008). Furthermore, it has been recently shown that DCs from RA patients with inactive disease express higher levels of FcγRIIB than active RA patients and healthy controls and that they inhibit TLR4 signaling, providing a novel mechanism as to how FcγRIIB exerts a regulatory role in immune responses (Wenink, Santegoets et al 2009). …”
Section: Molecular Interactions At the Dc-t Cell Interface That Contrmentioning
confidence: 92%
“…Consistently, an FcγRIIB defi ciency can lead to overwhelming infl ammation as evidenced by the increased susceptibility to EAE shown by FcγRIIB knockout mice (Kalergis and Ravetch 2002;Iruretagoyena, Riedel et al 2008). Furthermore, it has been recently shown that DCs from RA patients with inactive disease express higher levels of FcγRIIB than active RA patients and healthy controls and that they inhibit TLR4 signaling, providing a novel mechanism as to how FcγRIIB exerts a regulatory role in immune responses (Wenink, Santegoets et al 2009). …”
Section: Molecular Interactions At the Dc-t Cell Interface That Contrmentioning
confidence: 92%
“…Coherently, APCs from RA patients have been shown to produce more TNF upon IC triggering than healthy control APCs, which can be explained by increased expression of Fc RII and Fc RIII on these cells [92,93]. High expression of the inhibitory Fc RIIb could play an important role in controlling inflammation by inhibition of activating Fc Rs and TLR4 induced cytokine production in macrophages and DCs [5,94]. Highly increased Fc RIIb expression on monocyte-derived DCs from RA patients that have sustained low disease activity without the need of medication underscores the importance of this feedback mechanism in RA [5].…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…High expression of the inhibitory Fc RIIb could play an important role in controlling inflammation by inhibition of activating Fc Rs and TLR4 induced cytokine production in macrophages and DCs [5,94]. Highly increased Fc RIIb expression on monocyte-derived DCs from RA patients that have sustained low disease activity without the need of medication underscores the importance of this feedback mechanism in RA [5].…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
See 1 more Smart Citation
“…Monocytederived DC, but not monocytes, for instance, from RA patients who discontinue the use of disease-modifying antirheumatic drugs express higher levels of the anti-inflammatory FCgRIIb but equal levels of the inflammatory FcgR [29]. FcgR recognize the Fc portion of IgG antibodies and depending on the type of receptor that is engaged, Fc receptors have been shown to mediate either inflammatory or antinflammatory responses after ligation of immunocomplexes (IgG-antigen conjugates) [30].…”
Section: Semi-mature DC Can Be Tolerogenicmentioning
confidence: 99%